2010
DOI: 10.1007/s12223-010-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent molybdenum reduction to Mo-blue by Acinetobacter calcoaceticus

Abstract: A local molybdenum-reducing bacterium was isolated and tentatively identified as Acinetobacter calcoaceticus strain Dr.Y12 based on carbon utilization profiles using Biolog GN plates and 16S rDNA comparative analysis. Molybdate reduction was optimized under conditions of low dissolved oxygen (37 degrees C and pH 6.5). Of the electron donors tested, glucose, fructose, maltose and sucrose supported molybdate reduction after 1 d of incubation, glucose and fructose supporting the highest Mo-blue production. Optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 32 publications
4
60
0
Order By: Relevance
“…Based on previous studies, the phosphate concentration required is around 5 mM and lower for optimal Mo-reduction [13,15,18,23,28,[30][31][32][33][34][35][36][37]39]. The result of the present study showed that maximum concentration of phosphate also occurred at 5.0 mM.…”
Section: Effect Of Phosphate and Molybdate Concentration On Moreductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Based on previous studies, the phosphate concentration required is around 5 mM and lower for optimal Mo-reduction [13,15,18,23,28,[30][31][32][33][34][35][36][37]39]. The result of the present study showed that maximum concentration of phosphate also occurred at 5.0 mM.…”
Section: Effect Of Phosphate and Molybdate Concentration On Moreductionsupporting
confidence: 58%
“…strain Dr.Y2 [36], S. marcescens strain Dr.Y6 [29], Serratia sp. strain Dr.Y5 [37], Enterobacter sp. strain Dr.Y13 [18], Acinetobacter calcoaceticus [37], Bacillus sp.…”
Section: Effect Of Phosphate and Molybdate Concentration On Moreductionmentioning
confidence: 99%
“…The determination of phosphate and molybdate concentrations supporting optimal molybdenum reduction is important because both anions have been shown to inhibit Mo-blue production in bacteria (Shukor et al, 2008a;Shukor et al, 2009a;Yunus et al, 2009;Shukor et al, 2009b;Shukor et al, 2010a;Shukor et al, 2010b;Lim et al, 2012;Ahmad et al, 2013;Othman et al, 2013;. The optimum concentration of phosphate occurred at 5 mM with higher concentrations were strongly inhibitory to reduction (Figure 1d).…”
Section: Effect Of Phosphate and Molybdate Concentrations To Molybdatmentioning
confidence: 97%
“…strain Dr.Y5 (Rahman et al, 2009), Enterobacter sp. strain Dr.Y13 (Shukor et al, 2009a), Acinetobacter calcoaceticus strain Dr.Y12 (Shukor et al, 2010b), prefer glucose as the electron donor, while Enterobacter cloacae strain 48 (Ghani et al, 1993), Serratia sp. strain Dr.Y5 (Rahman et al, 2009), S. marcescens strain Dr.Y9 (Yunus et al, 2009) and S. marcescens strain DRY6 (Shukor et al, 2008a) prefer sucrose as the best electron donor.…”
Section: Mo-blue Production Using Various Electron Donorsmentioning
confidence: 99%
See 1 more Smart Citation